Rapid in-situ growth of gold nanoparticles on cationic cellulose nanofibrils: Recyclable nanozyme for the colorimetric glucose detection. (1st February 2021) - Alle, Madhusudhan; Park, Soo Chan; Bandi, Rajkumar; Lee, Seung-Hwan; Kim, Jin-Chul
Highlights: Rapid in-situ growth of positively charged AuNPs on cationic cellulose nano fibrils. Cationic cellulose nanofibrils (C.CNF) were used as reducing and supporting agent. Entire synthesis process is ultrafast (30 s) and produce monodisperse AuNPs. AuNPs@C.CNF film was potentially reused for the glucose detection up to five cycles. Analysis of human serum samples and comparable with standard method. Abstract: Novel microwave-assisted green in-situ synthesis of positively charged gold nanoparticles (AuNPs) supported by cationic cellulose nanofibrils (C.CNF) within 30 s and devoid of additional reducing agent is reported. Peroxidase activity of these positive AuNPs was studied and that appeared to be superior over its negative charged counterpart. Further the AuNPs@C.CNF is casted into a film which makes it reusable. Using TMB substrate, simple and sensitive colorimetric detection methods for H2 O2 and glucose were established. Under optimal conditions, the linear ranges were found to be 0.5–30 μM and 1–60 μM, and the detection limits were 0.30 and 0.67 μM for H2 O2 and glucose, respectively. The film was potentially reused for the detection of glucose up to five cycles without a decrease in the activity. Further, this technique was employed to quantify glucose in human serum samples, and the obtained results were comparable with those of the standard GOD-POD method.